2013
DOI: 10.1002/sia.5314
|View full text |Cite
|
Sign up to set email alerts
|

Study on growth rate of TiO2 nanostructured thin films: simulation by molecular dynamics approach and modeling by artificial neural network

Abstract: Effects of the deposition process parameters on the thickness of TiO 2 nanostructured film were simulated using the molecular dynamics (MD) approach and modeled by the artificial neural network (ANN) and regression method. Accordingly, TiO 2 nanostructured film was prepared experimentally with the sol-gel dip-coating method. Structural instabilities can be expected, due to short-and/or long-range intermolecular forces, leading to the surface inhomogeneities. In the MD simulation, the Morse potential function w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In the bulk and surface regions, where bonds between the monomers are randomly oriented the monomer motion is isotropic and relaxation time is lower in comparison with contact and transition regions. A similar conclusion was reported by Borodin et al for the local relaxation of polyethylene oxide (PEO) at the TiO 2 surface [33].…”
Section: Dynamical Propertiessupporting
confidence: 69%
See 4 more Smart Citations
“…In the bulk and surface regions, where bonds between the monomers are randomly oriented the monomer motion is isotropic and relaxation time is lower in comparison with contact and transition regions. A similar conclusion was reported by Borodin et al for the local relaxation of polyethylene oxide (PEO) at the TiO 2 surface [33].…”
Section: Dynamical Propertiessupporting
confidence: 69%
“…It is concluded that the influence of the TiO 2 surface molecules on the conformational relaxation of the PANI is local: It is controlled by the first adsorption layer extending up to only 7 Å from the surface, but for torsion angles beyond 18-37 Å, it is identical to that in the bulk region of the PANI. In the contact region, relaxation time is higher than that of other regions because of the low mobility of PANI chains near the TiO 2 substrate, introduced as slowing-down effect [33,66]. Thus, an anisotropic motion is expected near the polymer-substrate interface, where the monomer ordering in the xy-plane results in a preferential monomer motion in that plane.…”
Section: Dynamical Propertiesmentioning
confidence: 98%
See 3 more Smart Citations